Analisis Perbandingan Perlindungan Hukum bagi Pejalan Kaki di Bandung, Indonesia dan Suwon, Korea Selatan - Sari, Rizkita Kurnia (CIC Lembaga Riset dan Konsultan Sosial, 2025)
Bandung and Suwon were designated as sister cities on August 25, 1997. They were chosen as sister cities because they share several similarities, including their status as centers of education and innovation, their development as smart cities, their rich cultural values, and their deep historical backgrounds. Both cities are also strategically located. Urban development in Bandung and Suwon focuses on efforts to create cities that are comfortable to live in by ensuring safety and convenience for their residents. This study aims to analyze and compare the legal protection provided to pedestrians in the cities of Bandung and Suwon. Pedestrians are among the most vulnerable road users, often exposed to accidents and violations of their rights to public space. In Bandung, there is currently no regional regulation that specifically governs legal protection for pedestrians. In contrast, the Suwon city government has implemented a range of progressive policies, including pedestrian priority zones and national laws that safeguard pedestrian rights. The research employs a normative juridical method with a qualitative descriptive-comparative approach. The findings reveal that Suwon demonstrates a significantly higher level of effectiveness in implementing pedestrian protection regulations compared to Bandung. Legal certainty in Suwon is supported by clear, written, and consistently enforced regulations, whereas Bandung continues to face challenges related to the clarity and consistency of legal enforcement in practice. This study recommends that Bandung adopt Suwon’s best practices to strengthen legal protection for pedestrians.